An Empirical Study on the Factors Influencing the Number of Fans of Female-Oriented Accounts on Chinese Tik Tok - Du, Yanyan; Lin, Shengliang; Zhang, Xueli (Frontiers in Psychology, 2022)
This paper selects 500 samples through a recommendation algorithm and, on the basis of content analysis, examines the factors that affect the number of fans of female-oriented accounts on Chinese TikTok in terms of intrinsic attributes, surface form, and deep content. The results show that in order to increase the number of fans of female-oriented accounts on Chinese TikTok, there are four variables of the intrinsic attribute with statistically significant differences, 13 variables of the surface form with statistically significant differences, and 9 variables of the deep content with statistically significant differences. Beauty-related content is not the best means to attract fans. It requires TikTok creators to get rid of stereotyped and conceptual female impressions, display the rich social roles of women, and build true, complete, and harmonious female images in innovative ways in accordance with the humanistic communication concept.